Design and Optimization of Targeted Liposomes for Delivery of Resveratrol from Polygonum cuspidatum for Treatment of Alzheimer’s disease - Jahnavi, Patibandla; Suneetha, A.; Arya, Renu; Vats, Sheetal; Kaur, Ramandeep; Parvez, Nayyar; Shakil Shaikh, Shoheb; Jayasingh Chellammal, Hanish Singh (Journal of Neonatal Surgery, 2025)
Background and Objective: The neurodegenerative condition known as Alzheimer's disease (AD) causes cognitive decline and memory loss over time. The polyphenolic chemical resveratrol, derived from the plant Polygonum cuspidatum, has antioxidant and neuroprotective effects. But its low bioavailability and solubility restrict its use in clinical settings. The purpose of this research was to improve the therapeutic effectiveness of resveratrol against AD by creating, optimizing, and characterizing folic acid-functionalized liposomes for targeted brain delivery of the compound. Materials and Methods: The ethanol-based extraction of resveratrol from Polygonum cuspidatum yielded 1.85% w/w. The process of thin-film hydration followed by sonication was used to prepare the liposomes. For the purpose of optimizing the formulation, phosphatidylcholine and cholesterol were used as independent variables in a 3² factorial design. To enhance their targeting of folate receptors, liposomes were functionalized with folic acid using carbodiimide chemistry. The enhanced liposomes were studied for their size, zeta potential, efficiency of entrapment, and release in vitro. We tested SH-SY5Y cells for cellular absorption, neuroprotective effectiveness, and amyloid-beta inhibition. Results: The optimized mixture showed an entrapment efficiency of 81.3 ± 2.4%, a zeta potential of -28.5 ± 1.2 mV, and a particle size of 142.8 ± 4.6 nm. Sustained release was shown in in vitro release experiments for up to 24 hours (84.7 ± 3.2%). The cellular absorption of folic acid-conjugated liposomes was 2.30 times more than that of non-targeted liposomes. The MTT test showed that there was substantial protection against Aβ-induced neurotoxicity (cell viability: 87.6 ± 2.1%). Reducing Aβ aggregation by 62.4 ± 3.8% was also a notable result of targeted liposomes. Conclusion: In vitro, folic acid-functionalized liposomes showed encouraging neuroprotective efficacy and improved resveratrol transport to the brain. The efficacy of this delivery system as a treatment for Alzheimer's disease needs more in vivo testing.